Kajian Pendekatan Struktural: Analisis Puisi "Akulah Medan" Karya Teja Purnama Lubis - Nursalassaty, Nursalassaty; Kairunnisa, Nia; Yani, Indri; Panjaitan, Roy Pandapotan (Indo-MathEdu Intellectuals Journal, 2025)
Understanding the meaning of a poem correctly requires an in-depth analysis of both intrinsic and extrinsic structures. The purpose of this study is to analyze the intrinsic structure of poetry which includes the physical structure and the inner structure of the poem. This analysis is carried out by dissecting the meaning of the use of words and the tone reflected in them. This study uses a qualitative descriptive method with several stages such as literature study, data analysis in the form of texts in poetry, and data validity tests. The main source of data from this study is the poem 'Akulah Medan'. The data collection process is carried out by collecting data in the form of words and phrases in poetry that refer to several aspects in the structural approach and then grouped into several parts. In this study, it was found that in terms of the physical structure of poetry using diction, rhyme, typography, imagination, concrete words, and distinctive language styles reflecting its authenticity to the history and cultural values of the city of Medan. Meanwhile, in terms of the inner structure of the poem, there are aspects of theme, tone, message, and taste in the poem that depict a firm, strong and emotional impression. This poem also depicts pride, loyalty and love for the city of Medan.